Patient’s satisfaction on meal service by outsourced foodservice contractors at government hospitals in Selangor / Mohd Harrith Hardeenata Abd Patah - Abd Patah, Mohd Harrith Hardeenata (2013)
Undeniable, hospital food and nutrition services play an important role in patient recovery and well-being. Meal service is one of the factors that influence satisfaction among hospitalized patients. This study empirically investigates the meal service attributes that associated with the satisfaction among patients at Hospital Selayang, Hospital Serdang and Hospital Sungai Buloh. By using the quantitative approach, the experiences of 236 patients were obtained. Through a series of descriptive and inferential statistics, some meaningful insights on the issues of interest were acquired. Findings of this study clearly revealed that food properties, interpersonal service and environmental presentation were recognized as contributory factors that influence patient satisfaction. Among these dimensions, food properties were the most important predictor in patient’s satisfaction, followed by interpersonal service and environmental presentation. The pessimistic indication has given some implications not only for the patients, but also for the outsourced foodservice contractors and hospitals as a whole.